Aplicación de brasinoesteroides y sus análogos en el cultivo de arroz (Oryza sativa L), bajo riego en el sector San Agustín de Chilintomo- Guayas” - Zambrano García, Adalberto Gregorio (2020)
The present experimental work was carried out at km, 14,5 of the Babahoyo-Mata de Cacao road: “San Agustín” Campus; with geographic coordinates of 79º 26´ West Longitude and 1º56´ south latitude belonging to the province of Guayas, INIAP 11 was used as planting material, The treatments consisted of the different levels of the foliar fertilizer Gibberellic acid + Indol-3-ylacetic acid + Brassinolide, in doses of 10, 20, 30 and 40 g / ha; plus a control treatment without application, The Randomized Complete Blocks experimental design with five treatments and 4 repetitions was used, the significance test used was Tukey's 95% probability, All the necessary agricultural work was carried out in rice cultivation for its normal development, such as soil preparation, sowing, irrigation, fertilization, weed control, phytosanitary control and harvesting, To estimate the effects of the treatments, the following data were taken: plant height, number of tillers, number of panicles, length of panicles, grains per panicles, weight of 1000 grains, yield, economic analysis, Based on the results obtained, it was determined that in the variable weight of 1,000 seeds, the T2 treatment with a dose of 20 g / ha showed highly significant differences with respect to the treatment without application, Regarding yield, the best behavior was presented by treatment T2 with the dose of 20 g / ha, which obtained the highest yield 7228,35 grams, being statistically equal to treatments T3 and T4, but much superior to treatment T5 (control), Through the economic analysis it was found that the best economic performance was obtained with the T2 treatment with a dose of 20 g / ha with $ 1289,61